2011
DOI: 10.3109/00365521.2011.565066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic fermented milk on symptoms and intestinal flora in patients with irritable bowel syndrome: A randomized, placebo-controlled trial

Abstract: During this 8-week trial gastrointestinal symptoms improved. However, there was no difference between treatment with fermented milk containing probiotics or acidified milk. The effect of probiotics on IBS symptoms remains uncertain and further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(136 citation statements)
references
References 15 publications
0
132
0
3
Order By: Relevance
“…Significant pain alleviation was not found in 16 studies (6,19,20,(22)(23)(24)(25)(26)29,32,34,(36)(37)(38)(39), although a pain alleviation trend was found in 4 studies (5,23,32,37). Both the TG and Studies identified from bibliographic databases n = 252…”
Section: Abdominal Pain or Discomfortmentioning
confidence: 99%
“…Significant pain alleviation was not found in 16 studies (6,19,20,(22)(23)(24)(25)(26)29,32,34,(36)(37)(38)(39), although a pain alleviation trend was found in 4 studies (5,23,32,37). Both the TG and Studies identified from bibliographic databases n = 252…”
Section: Abdominal Pain or Discomfortmentioning
confidence: 99%
“…Patients taking probiotics did not have any significant increases in intestinal microbiota or changes in levels of the inflammatory marker C-reactive protein (15). Another study reported that patients taking a probiotic mixture containing B. lactis and those taking placebo had similar improvements in gastrointestinal symptoms after 8 weeks (16). One controlled study observed that a group taking synbiotic yogurt (including B. lactis Bb12 and acacia fiber) had significant improvements and recovery in the initial symptoms of constipation-predominant and diarrhea-predominant IBS than did those taking standard yogurt as a control (17).…”
Section: Discussionmentioning
confidence: 98%
“…Ford ; B. infantis 35624 60,61 ; VSL #3 [62][63][64] ; a combination product of L. paracasei subspecies paracasei F19, L. acidophilus La5, and B. lactis Bb12 [65][66][67] ; and the other combination of B. lactis DN-173 010, S. thermophilus, and L. bulgaricus. 68,69 A systematic review of 18 RCTs involving 1806 IBS patients and consensus voting reported a high grade of evidence for the effect of probiotics on abdominal pain, and a good consensus agreement.…”
Section: Global Efficacy Of Probiotics In Irritable Bowel Syndrome: Dmentioning
confidence: 99%